(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3HGH GdOGd hGdMGA heG HYOgeG (B: (3GdCSeGA aYd HaJM GdaGA hSchf GdYjf s
(3BNQgG (B:s
(3BNQg eHJhQ , hGdehLhO efg ef HGH GdTjf hGdgeRI heG HYOgeG bhdg (B: (3GdTCR HGdRGi Gdbdb Tjag TCakG hTjfJ EPG NQL ajgG GdTGaI s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjjf HGdMeQIs
(3hYdi MhGTjgG ebGHdGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs